2005
DOI: 10.1177/1470595805054489
|View full text |Cite
|
Sign up to set email alerts
|

Does National Culture Affect Willingness to Justify Ethically Suspect Behaviors?

Abstract: In this article, we examine the relationship of the Global Leadership and Organizational Behavior Effectiveness national culture dimensions with the willingness of 27,459 individuals located in 21 nations to justify ethically suspect behaviors. Hierarchical Linear Modeling (HLM), a technique well suited for cross-level studies, is employed to test the hypothesized relationships from data made available by the World Values Survey. Results support our hypotheses with regard to performance orientation, assertiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 37 publications
3
82
1
1
Order By: Relevance
“…A small number of studies have examined the relationship between human orientation and ethical behaviour. Parboteeah et al (2005) found that human orientation is negatively associated with a willingness to justify ethically suspect behaviours, probably due to the nurturing and cooperative nature of this type of society. Moreover, Alas (2006) includes human orientation as one of the characteristics of societies which have low needs for well-established standards for ethics.…”
Section: Moderating Role Of Culture In Sars-ebf Relationshipmentioning
confidence: 98%
See 3 more Smart Citations
“…A small number of studies have examined the relationship between human orientation and ethical behaviour. Parboteeah et al (2005) found that human orientation is negatively associated with a willingness to justify ethically suspect behaviours, probably due to the nurturing and cooperative nature of this type of society. Moreover, Alas (2006) includes human orientation as one of the characteristics of societies which have low needs for well-established standards for ethics.…”
Section: Moderating Role Of Culture In Sars-ebf Relationshipmentioning
confidence: 98%
“…Compared to Hofstede's study (2001), GLOBE is considered to be both more recent and comprehensive (Shi and Wang 2011). Moreover, its methodology is found to have greater validity and reliability (Parboteeah et al 2005).…”
Section: Moderating Role Of Culture In Sars-ebf Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Brodbeck et al, 2000;Javidan & Dale, 2005;Parboteeah, Bronson, & Cullen, 2005) or, conversely, have focused on organizational characteristics and leadership behaviours. For instance, the relationships between organizational culture and leadership behaviours have received considerable attention within specific countries (e.g.…”
Section: Q3mentioning
confidence: 99%